(3GdHQgGf aj Ydhe GdbQBfs - (3Ydj Hf EHQGgje Hf SYjO, CHh GdMSf GdMhaj,J (B430 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ bhdg JYGdi (B" (3hCeG GdPjf SYOhG aai GdLfI (B" (3ef ShQI ghO s
(3BNQgG (B:s
(3hjfJgi Hbhdg JYGdi (B:" (3ddPjf CSJLGHhG dQHge GdMSfi (B" (3ef ShQg GdQYO s
(3ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B250 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B5s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B23 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdJaSjQ hYdhe GdbQBfs